Word Formation on Slang Words in Boost’s Instagram Captions and Posts Targeting Teenagers - Michelle Evangeline (Institute of Research and Community Outreach - Petra Christian University, 2023)
The study analyzed captions and posts on Boost’s Instagram that utilizes English slang to communicate to the target market. It used the theories of types of word formation processes by Yule (2006) and that by Minkova and Stockwell (2009). The findings found only the following types of word formation processes: coinage, compounding, blending, clipping, conversion, acronym, derivation, other sources, and multiple processes, with acronym as the most commonly used. Obviously, borrowing and backformation are the types of word formation processes that were not found in the data. It may also be concluded that the targeted reader may influence the use of a certain type of word formation process.